Proposed sports training program and its effect on developing speed endurance in middle-distance runners aged [16-18] years - trich, lahcen; layadi, abdelkrim (sports creativity, 2025)
Sports training is among the most commonly used terms among athletes, as it involves gradual mental and physical progress over several years in order to achieve the result. The athlete goes to the field to satisfy his needs in exercising his body to become strong, fast, enduring and flexible, and to make it capable of absorbing the special movement technique. He is forced to take care of this body and monitor its performance, weight and development, as well as think about the best way to feed it. If a runner wants to outperform his competitors, he must have tremendous mental and physical capabilities. Through this concept, we can see how difficult and complex the training method is to achieve all these requirements, because the latter also helps a great deal in the runner reaching the high level, or as Arnhem and Claves said: training is the organized process of repetition and progress in exercise or work that also contains the process of learning and adaptation ( ). The age period from 23 to 30 years is sometimes considered the golden age in the life of the runner, as its results reach the highest levels. For this purpose, the selection process for runners must be carried out in a systematic and organized manner based on scientific foundations and at an early age towards the specialization that is appropriate for them. After that, a dedicated training program is drawn up and distributed over several years, as follow-up also plays an essential role in stabilizing the athlete’s form at this level. In this regard, we prepared a study entitled “Proposing a sports training program and its effect on developing the quality of speed endurance in middle-distance runners in the [16-18] age group,” which is a field study of the State of M’sila Athletics Club (OSAM), as we chose it because it plays a major role in developing this specialty, in particular, and athletics in general, and because we believe that the beginning of the specialty is at this age and with this particular physical quality.